2020
DOI: 10.11591/ijeecs.v21.i2.pp1176-1184
|View full text |Cite
|
Sign up to set email alerts
|

Classification techniques’ performance evaluation for facial expression recognition

Abstract: <p><span>Facial exprestion recognition as a recently developed method in computer vision is founded upon the idea of analazing the facial changes in which are witnessed due to emotional impacts on an individual. This paper provides a performance evaluation of a set of supervised classifiers used for facial expression recognition based on minimum features selected by chi-square. These features are the most iconic and influential ones that have tangible value for result dermination. The highest ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Pooling is a key phase in lowering the dimensions of the map of activation, retaining just the necessary elements while minimizing spatial invariance. As a result, the model's learnable features are reduced [38]. This contributes to the resolution of the overfitting issue.…”
Section: Poolingmentioning
confidence: 99%
“…Pooling is a key phase in lowering the dimensions of the map of activation, retaining just the necessary elements while minimizing spatial invariance. As a result, the model's learnable features are reduced [38]. This contributes to the resolution of the overfitting issue.…”
Section: Poolingmentioning
confidence: 99%
“…Performance of DRL techniques can be improved by adopting neural networks to approximate the function efficiently, thereby, enhancing its capability to handle both, large state and action spaces [15]. Particularly, multilayer concept (MLP) is chosen as a predictive tool for this study showed promising results in applications of financial forecasting [8], [15], power forecasting [42], attack detection [43]- [45], facial expression recognition [46] and wind speed prediction [47]. Here, MLP is used to describe time arrangement information that attempts to predict the near distant future information dependent on its past information.…”
Section: Multilayer Perceptron (Mlp)mentioning
confidence: 99%
“…The Internet of Things makes use of the Internet as a global networking environment for a broad range of physical things, which enables it to promote the wireless transmission of data and interaction between those physical devices. The information and data we have are very important to our day-to-day existence [40], [41]. There is a pervasive information-driven perspective on today's corporate systems, as seen by the proliferation of IoT and service-oriented enterprise structures, social networks, smart portable devices, and intelligent automobiles.…”
Section: Introductionmentioning
confidence: 99%